Case Report: Empowering Mothers, Protecting Newborns (The Role of Midwifery Continuity of Care in Promoting Exclusive Breastfeeding During Mother-Infant Separation) - Ningtyas, Woro Setia; Lovita, Agnestia Naning Dian; Setyowati, Dewi; Rohma, Annisa Nur (Women, Midwives and Midwifery, 2026)
Background: exclusive breastfeeding (EBF) is critical for neonatal health, but complications like jaundice can disrupt early feeding due to mother-infant separation. Midwifery Continuity of Care (MCoC), where a known midwife provides consistent support throughout the perinatal period, may play a crucial role in maintaining EBF during such challenges. This case report aims to explore the role of MCoC in sustaining exclusive breastfeeding during mother-infant separation due to neonatal jaundice. Case Presentation: a 29-year-old woman (G2P1A0) received MCoC from early pregnancy through postpartum. After a cesarean delivery due to preeclampsia, her newborn developed jaundice with a total bilirubin level of 15.31 mg/dL and an index bilirubin of 14.96 mg/dL. It required 48 hours of phototherapy and NICU admission. Despite separation, the mother sustained lactation through regular milk expression, supported by her midwife, husband, and family. The mother had received education from the midwife about the importance of breastfeeding for the baby, starting from pregnancy until after delivery. The continuous presence and support of the midwife empowered the mother to remain consistent in expressing breast milk until the baby’s condition improved, allowing the infant to continue receiving exclusive breastfeeding. After receiving phototherapy, the infant’s bilirubin level decreased to 9.82 mg/dL and the baby was discharged in stable condition. Exclusive breastfeeding was successfully continued post-discharge Discussion: this case highlights the important role of MCoC in supporting successful exclusive breastfeeding in infants with neonatal jaundice. Through ongoing education and support, midwives help mothers continue to provide expressed breast milk during phototherapy, which contributes to lowering bilirubin levels. The MCoC approach strengthens mothers' confidence and emotional resilience, while also increasing breastfeeding success in complex medical conditions Conclusion: MCoC is a valuable model for supporting EBF during mother-infant separation caused by jaundice. It empowers mothers through continuous clinical, emotional, and educational support, ensuring continuity of care and improved breastfeeding outcomes. This case underscores the importance of integrating MCoC into midwifery practice and policy to enhance breastfeeding outcomes and maternal-infant health